(untitled) (Journal of the College of Basic Education, 2026)
This research examines the role of the Iraqi Ministry of Industry in developing industrial plants during the period 1967–1968. This period witnessed increased state interest in strengthening the industrial sector as a cornerstone of economic development. This historical and documentary study relies on available Ministry of Industry documents pertaining to the establishment and development of industrial companies and plants during 1967–1968. These documents have never been published before. Despite studies of the industrial landscape in Iraq, significant aspects of this field of historical research remain unexplored and have not yet received the attention they deserve according to the principles of historical methodology. The documents included in this research are official correspondence and decisions concerning the establishment of some industrial companies and plants, as well as changes in the management of others. The research aims to trace the historical role played by the Ministry of Industry in advancing industrial projects in Iraq, drawing on previously unpublished Ministry of Industry documents and presenting them objectively. Through the analysis and presentation of these Ministry of Industry documents for the years 1967–1968, the Ministry’s role in establishing and developing companies and plants can be clearly defined. Industrial.